2017
DOI: 10.1097/qmh.0000000000000135
|View full text |Cite
|
Sign up to set email alerts
|

Evidence-Based Practice Standard Care for Acute Pain Management in Adults With Sickle Cell Disease in an Urgent Care Center

Abstract: Background:Vaso-occlusive episodes (VOEs) with sickle cell disease (SCD) require opioid treatment. Despite evidence to support rapid pain management within 30 minutes, care for these patients does not consistently meet this benchmark. This quality improvement study sought to decrease the first analgesic administration time, increase patient satisfaction, and expedite patient flow.Methods:A prospective pre-/postevaluation design was used to evaluate outcomes with patients 18 years or older with VOEs in an urgen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(24 citation statements)
references
References 28 publications
0
24
0
Order By: Relevance
“…Five different studies (Bernier et (Kim et al, 2017) reported improvement (not statistically significant) in knowledge and awareness of rapid pain management within 30 min of triage and sustained six months postimplementing the use of EBPSC algorithm.…”
Section: Outcome 1: Positive Improvement In Knowledgementioning
confidence: 99%
See 1 more Smart Citation
“…Five different studies (Bernier et (Kim et al, 2017) reported improvement (not statistically significant) in knowledge and awareness of rapid pain management within 30 min of triage and sustained six months postimplementing the use of EBPSC algorithm.…”
Section: Outcome 1: Positive Improvement In Knowledgementioning
confidence: 99%
“…Two studies (Kim et al, 2017;Yacoub et al, 2019) and planned conferences and retreats (Haywood et al, 2015). One study did not report the length of interventions (Hanik et al, 2014).…”
Section: Study Interventions and Strategies For Implementationmentioning
confidence: 99%
“…Therefore, using individualized opioid dosing with earlier administration of early analgesia with a maximum opioid dose would result in a shorter hospital stay [ 24 ]. Kim et al evaluated outcomes in SCD patients during VOEs in an urgent care (UC) center following implementation of evidence-based practice standard care (EBPSC), including the meantime for administering the first analgesic dose, the mean length of stay, and overall patient’s satisfaction, and concluded that implementing EBPSC had resulted in improvement in the management of VOEs as well as provided patients with positive experiences [ 25 ].…”
Section: Reviewmentioning
confidence: 99%
“…A seminar study conducted by Kim, Brathwaite and Kim (2017) to investigate rapid pain management for individuals with SCD suggests the implementation of Evidence-Based Practice Standard Care (EBPSC) as a crucial step for improving the management of VOEs. In that, EBPSC enhances the quality of care in the SCD population.…”
Section: Defining Sickle Cell Diseasementioning
confidence: 99%